Study of 1D Strange Charmed Meson Family Using HQET - Pallavi Gupta; A. Upadhyay (Advances in High Energy Physics)
Recently LHCb predicted spin 1 and spin 3 states Ds1⁎(2860) and Ds3⁎(2860) which are studied through their strong decays and are assigned to fit the 13D1 and 13D3 states in the charm spectroscopy. In this paper, using the heavy quark effective theory, we state that assigning Ds1⁎(2860) as the mixing of 13D1-23S1 states is rather a better justification to its observed experimental values than a pure state. We study its decay modes variation with hadronic coupling constant gxh and the mixing angle θ. We appoint spin 3 state Ds3⁎(2860) as the missing 1D  3-JP state and also study its decay channel behavior with coupling constant gyh. To appreciate the above results, we check the variation of decay modes for their spin partners states, that is, 1D2 and 1D2′, with their masses and strong coupling constant, that is, gxh and gyh. Our calculation using HQET approach gives mixing angle of the 13D1-23S1 state for Ds1⁎(2860) to lie in the range (-1.6 radians ≤θ≤-1.2 radians). Our calculation for coupling constant values gives gxh to lie within value range of 0.17–0.20 and gyh to be 0.40. We expect from experiments to observe this mixing angle to verify our results.